(untitled) (mathematica didactica, 2007)
Diagnostic competence characterizes the current discussion about standards in the teaching profession. This involves the expectation of already combining diagnostics and support effectively during the learning process itself. Adequate problems are of particular importance. The following article illustrates the relevance of the construction and evaluation of problems which are guided by a profound theory.